Preliminary Outcomes of a Cross‐Site Cognitive–Behavioral and Neuromuscular Integrative Training Intervention for Juvenile Fibromyalgia. Issue 3 (March 2017) - Tran, Susan T.; Guite, Jessica W.; Pantaleao, Ashley; Pfeiffer, Megan; Myer, Gregory D.; Sil, Soumitri; Thomas, Staci M.; Ting, Tracy V.; Williams, Sara E.; Edelheit, Barbara; Ounpuu, Sylvia; Rodriguez‐MacClintic, Jennifer; et al.
Abstract : Objective: Cognitive–behavioral therapy (CBT) is effective in reducing disability among youth with juvenile fibromyalgia (FM); however, engagement in moderate to vigorous physical activity remains poor, even after CBT. The purpose of this study was to evaluate the feasibility and preliminary outcomes of an innovative program combining CBT with specialized neuromuscular exercise: the Fibromyalgia Integrative Training for Teens (FIT Teens) program. Methods: Adolescents with juvenile FM (n = 22, all female, ages 12–18 years) from 2 urban children's hospitals participated in the 8‐week FIT Teens intervention. Participants completed measures of pain intensity, functional disability, depressive symptoms, pain catastrophizing, fear of movement, and readiness to change at baseline and after the intervention. Results: The feasibility of the intervention across 2 sites was documented, including high retention rates (80%). Participants showed significant decreases in functional disability ( P  < 0.05), depression ( P  < 0.001), fear of movement ( P  < 0.01), and pain catastrophizing ( P  < 0.001) from pre‐ to postintervention. Results of the readiness to change measure indicated a significant decrease in precontemplation ( P  < 0.01) and increase in action/maintenance scores ( P  < 0.001). All results demonstrated medium to large effect sizes. Conclusion: Adolescents with juvenile FM reported significant improvements in physical function and reduced fear of movement following the intervention. Improvement in physical function was achieved in a shorter time frame than in a prior trial of CBT without an exercise component. Further work is needed to compare the FIT Teens program with existing approaches and determine whether objective changes in exercise participation are achieved.